Agriculture in intergenerational relations: Ethnic Thai youth in northern Vietnam - Kawarazuka, Nozomi; Nguyen Thi Van Anh; Vu Xuan Thai (International Potato Center, 2021)
Ethnic minority youth are deeply embedded in reciprocal support with their parents through farming, even though young men are often absent, looking for casual labor work outside the village. Drawing on the concept of intergenerational relations, this study illustrates gendered experiences of a youth transition period with a specific focus on the interactions of youth with parents and parents-in-law through agriculture. Findings show that young men and women access cash, goods and services from their kin in exchange for unpaid labor in farming and domestic work. The economic focus of research on agriculture as a source of income masks this important aspect of agriculture within ethnic minority communities. Although married young men and women in their 20s are not the formal owners of farmlands and livestock, they actively negotiate with their parents and in-laws to utilize agricultural resources to their benefits. Unpaid youth labor in agriculture should be viewed as more than a simple problem of unemployment, a lack of formal access to farmland, or a lack of individual skills. Instead, gendered experiences of ethnically marginalized youth should be reflected in relevant policies and agenda settings to support youth agriculture embedded in intergenerational reciprocal relations.